Prediction of oxide scale growth in superheater and reheater tubes - Purbolaksono J.; Khinani A.; Rashid A.Z.; Ali A.A.; Nordin N.F. (2023)
In this paper a procedure on how to estimate the oxide scale growth in superheater and reheater tube utilizing the empirical formulae and the finite element modeling is proposed. An iterative procedure consisting of empirical formulae and numerical simulation is used to determine scale thickness as both temperature and time increase. Results of the scale thickness over period of time for two different design temperatures of the steam and different heat transfer parameters are presented. The procedures may provide better estimation on the oxide scale growth, provided that all the heat transfer parameters are well specified. 2009 Elsevier Ltd. All rights reserved.